Desempenho agronômico de feijão e milho em cultivo solteiro e consorciado, em função da população de plantas de feijão - Komuro, Lauro Kenji [UNESP] (2014)
Intercropping corn and winter common beans is an excellent alternative for the sustainable farming family in long term mainly because they can have diversity of the cultivations and maximization of the soil providing more economical return and a larger food supply. The study aimed to verify performance of common bean and corn in monocropping and intercropping as a function of population of common bean. The experiment was developed in 2010 and 2011 in the experimental area of the Regional center for Technological Development of Agribusiness of west Extreme (APTA) in Andradina-SP. IPR Colibri common bean cultivar were used in 2010, and IPR Juriti in 2011, in the population of 150,000, 175,000, 200,000 and 250,000 plants ha-1. In both years the maize cultivars Sol da Manhã and Dentado were used with population of 40.000 plants ha-1. The experimental design was randomized complete block with four replications. Both in monocrop system as in consortium with the corn cultivars Sol da Manha and Dentado, the variation in the population of the common bean plants IPR Colibri and IPR Juriti influences some traits yield components of common bean, nature grain corn and corn for grain, but do not influences the final yield of both crops. Therefore, under this item of view, regardless of cropping system and corn and common bean cultivars used in this study, the best population of common bean to be used is 150,000 plants ha-1, seeking cost savings the common bean seeds. However, taking into account the Index Equivalence of Area, the combination of Dentado corn with 175,000 plants ha-1 of common bean was the best. The bean cultivar IPR Colibri is best suited for consortium with maize for nature grain corn production because it is harvested before this